Cupology: How to Be Entertaining - Clara (Salt Lake City, UT : Project Gutenberg, 2008)
"Cupology: How to Be Entertaining" by Clara is a guidebook on social etiquette and entertainment techniques written in the early 20th century. The book explores various ways to enhance social gatherings, including the art of reading tea leaves for character assessment and fortune-telling, offering insights for both hosts and their guests. It is likely to appeal to readers interested in social customs, mysticism, and methods for creating engaging interactions during gatherings. The opening of the book introduces the concept of "cup-reading," a practice wherein the patterns formed in the dregs of tea or coffee are interpreted to gain insight into one's character and future. Clara shares a series of readings performed at a social gathering, where participants, eager to explore their futures, present their cups for interpretation. The readings reveal insights about the individuals' personalities, relationships, and hopes, setting the tone for this whimsical exploration of social enjoyment and the mystical elements that can add flair to any event. (This is an automatically generated summary.)
Release date is 2008-08-17
Produced by Ruth Hart
Keywords: Amusements; Fortune-telling